The Development of Car Workshop Inventory Management System for Thompson Auto Service Centre - Lau, Wei Xuen; Darman, Rozanawati (Applied Information Technology And Computer Science, 2025)
Car Workshop Inventory Management System is a web-based system that allows the car workshop to manage the products. The current existing system relies on the paper-based and excel spreadsheet method, which leads to problems with inaccuracies and missing items. In response, the proposed system is designed to enhance efficiency and accuracy of inventory management in car workshops. The study domain of this system is inventory management. The methodology that used to design the system is waterfall methodology. The users that are involved in this system are admin, clerks and mechanics. The owner as admin able to manage the users account by only adding new users or deleting existing users in the system. Admin also able to perform CRUD for the product and supplier information in the system. Admin also able to make decisions on approving or rejecting the order request made by clerks and able to view the monthly sales report in the system. As for clerks, clerks use the system to make a order request based on the product on low stock. Clerks able to view the result of the order request and make replenishment for the ordered product in the system. For mechanics, mechanics use this system to perform product takeout from the system only. The methodology that used for developing this system is waterfall methodology. The software that used for wireframe design is Miro and for developing this system is Visual Studio Code. In conclusion, the developed system empowers the workshop with the ability to make informed decisions and enhance operational effectiveness, aligning with the dynamic needs of the evolving automotive industry.